Realigning with the slave-like Jesus of Mark: The shorter ending of Mark 16:1-8 as a relecture - S. Joubert (Acta Theologica)
Mark’s shorter ending (16:1-8) is understood as a paratext, one that interrupts the existing text by forcing a relecture of the entire Gospel. It compels the intended readers to realign themselves with the provocative narration of Jesus as the atypical Messiah who challenges the physiognomic stereotypes of an honour-shame-based context. From this hermeneutical perspective, the reference text of Mark provokes a second text, the reception text, but does not replace it. Rather, it takes on motifs and themes of the first text as a kind of “interpretive development”. This new reception text, which is embedded in Mark’s original reference text, pushes the intended readers not only to re-read the Gospel, but also to re-understand it in light of Mark’s provocative presentation of the “non-godly” bodily demeanour of Jesus. However, it would appear that the original intertextual relecture, prompted by the ending of Mark 16:1-8, did not wholly succeed. Its open-ended nature, coupled with its provocative interpretation of Jesus, probably created too much dissonance for an unknown author who eventually added the longer ending of 16:9-20 in a different vocabulary and style.